Pengaruh Media Sosial terhadap Efikasi Keputusan Perjalanan Generasi Z dalam Memilih Destinasi Wisata di Jabodetabek - Sisilia Alvionita; Eveline Gaby Sutanto; Natasha Dyah Ayuningtyas; Nyoman Krisna Wati; Made Handijaya Dewantara (Politeknik Pariwisata NHI Bandung, 2021)
This study aims to determine the differences in social electronic word-of-mouth and travel motivation for Generation Z who are living in the Jabodetabek area. This research was conducted because it had never been done by previous researchers. The data collection used is by using a survey through Google Forms and literature studies from various journals. This study uses a quantitative approach by analyzing data through the IBM SPSS system. The results showed that there was a positive and significant relationship that the efficacy of generation Z travel decisions in choosing tourist destinations in the Jabodetabek area was influenced by the existence of the social electronic word of mouth and travel motivation. However, the differences in social electronic word-of-mouth and travel motivation among Generation Z who live in the Jabodetabek area are not homogeneous. Therefore, the calculation of the efficacy of their travel decisions also cannot be equated. The goals and motivations for the journey of Generation Z who live in Jakarta are not necessarily the same as Generation Z who live in other regions.